Analisis Nilai Karakter Pada Cerpen “Pohon Keramat” Karya Yus R. Ismail - Siti Suryani; Winda Siti Nabila (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
Literary works are depictions of the reality of life which are used as tools to express imagination and thoughts around them. In this research, the author aims to reveal the character values ​​contained in the short story entitled "Sacred Tree" by Yus R. Ismail and then relate them to real life. In his research, the author used a qualitative descriptive method, which in the process displays the data as it is without manipulation or other treatments. The aim of this research is to present a complete picture of an event or is intended to expose and clarify a phenomenon that occurs. The steps for collecting data in the short story "Sacred Tree" are by (1) reading the short story intensively, then (2) analyzing the character values ​​and (3) presenting the data. Apart from using qualitative descriptive methods, the author also uses a mimetic approach, namely research that connects the content of literary works and real life. In this short story the author finds character and moral values ​​depicted in each character, as well as a real storyline that occurs in life. A difference of opinion which then becomes the cause of a dispute, but can be resolved by a figure who has a wise nature. Then the policy leads to changes that cause regret in the future. And the moral value presented in this short story is not to force change on a group or person if we cannot be responsible for the change. This short story by Yus R. Ismail is a simple short story that describes real life clearly without engineering and contains several useful lessons for the reader.